Crop use and profile distribution of phosphorus in soils that developed on mafic rocks in southern Portugal. Issue 4 (21st March 2019) - Horta, Carmo; Monteiro, Fernando; Madeira, Manuel; Torrent, José
ABSTRACT: The phytoavailability of soil phosphorus (P) depends on the different forms in which it occurs and how these forms change after the application of P fertiliser to the soil. Forms of P in the A, B and C horizons of eleven pedons that developed on mafic rocks were characterised by a fractionation method before and after fertilisation with single superphosphate, and a micropot experiment was conducted to assess the short-term use of P fertiliser by rye ( Secale cereale L.). The main sources of P to the crop were (i) phosphate adsorbed on mineral surfaces and pedogenic Fe, Al or Ca phosphates in the A horizon and (ii) Ca-phosphates in B and C horizons. In the C horizons, poor in Fe/Al phases and clay, the precipitated Ca-P showed low solubility, resulting in a reduction in shoot biomass. The apparent P recovery by rye was similar in the A (36%) and B (29%) but decreased in the C (15%) horizons. The partial factor productivity (g g −1 ) decreased from the A (58) to B (11) and C (5) horizons. P phytoavailability decreased with increasing profile depth because the transformation of P fertiliser to poorly soluble Ca-P forms increased with depth.